PENGARUH GAYA KEPEMIMPINAN, BUDAYA KERJA, MOTIVASI TERHADAP DISIPLIN KERJA SERTA DAMPAKNYA TERHADAP KEMAMPUAN KERJA PEGAWAI DAN KINERJA DI PUSKESMAS SE-KOTA PANGKALPINANG - Ester Rohani Sitompul; Hamsani; Andriyansah (Universitas Lambung Mangkurat, 2019)
Government employees can serve the community must be professional, more transparent, faster in using time so they can build the quality of individuals and communities to actively determine their own future. This research was conducted at Pangkalpinang City Health Center Staff with a population of 524. The sample used was 84 respondents. The independent variables in this study are leadership style, work culture, motivation. while the dependent variable is work ability and performance which is moderated by Work Discipline. Variable measurements are carried out using an ordinal scale. Data analysis was performed by Multiple Linear Regression. The software used for analysis is SPSS 22. From the estimated standards for the variables of Leadership Style (X1), Work Culture (X2), Motivation (X3), Work Discipline (Y) then structural equations can be made as follows Y = 27,212 + 0.509 X1 + 0.220 X2 + 0.276 X3 + e. The influence of Work Discipline variables on Work Ability can be made equation Z = 11,361 + 0.727 Y + e. The influence of Work Discipline variables on Performance then the equation Z = 2,312 + 1,167 Y + e can be made. The results of the analysis show that work discipline variables are influenced by leadership style, work culture, motivation simultaneously or together 65.5% while the remaining 34.5% is influenced by other factors outside the research model. For the variable work ability is influenced by work discipline by 52.5% while the remaining 47.5% is influenced by factors outside this research model while the performance variable is influenced by work discipline by 79% while the remaining 21% is influenced by factors outside this research model.